Effects of plant growth regulators and basal media on Atractylodes macrocephala Koidz.'s shoot multiplication - Tai, Nguyen Thanh; Quyen, Phan Thuy; Nhi, Pham Thu; Thang, Pham Quang; Hung, Le Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Atractylodes macrocephala Koidz. belonging to the genus Atractylodes is a high-value medical plant with more than 79 phytochemical components. However, few studies about the miropropagation protocol of this species are conducted in Vietnam. The purpose of this study is to investigate the effects of some PGRs and basal media on Atractylodes macrocephala Koidz's in vitro shoot multiplication viewed as the most critical stage in the miropropagation protocol. In this study, stem nodes with dorminant shoots were cultured on different media after selecting an optimized medium from experiments supplemented with BA in combination with IBA with different concentrations. After four weeks of culture, the highest number of shoots on MS medium containing 1 mg/L BA in combination with 0.3 mg/L IBA was 2.18 shoots/explant. Interestingly, the optimized medium for AM's in vitro shoot proliferation was 1/2MS medium supplemented with 1 mg/L BA in combination with 0.3 mg/L IBA. The highest number of shoots reached at 14.5 shoots/explant being more than 4 times compared to the results of the previous studies. The result significantly contributes to the efficient micropropagation of Atractylodes macrocephala Koidz. for comercial production.